Guidance on the critical shortage of sodium citrate coagulation tubes for hemostasis testing. (2nd September 2021) - Gosselin, Robert C.; Bowyer, Annette; Favaloro, Emmanuel J.; Johnsen, Jill M.; Lippi, Giuseppe; Marlar, Richard A.; Neeves, Keith; Rollins‐Raval, Marian A.
Abstract: Recent manufacturing problems and increased utilization has created a shortage of 3.2% sodium citrate blood collection tubes used for coagulation testing, causing stakeholders such as hospitals, clinics and laboratories, to find suitable alternatives. Considerations for in‐house citrate blood collection tube preparations or purchasing commercial products from unknown manufacturing sources is of particular concern to laboratories that perform coagulation testing. It is well recognized that variability exists between citrate blood collection tube manufacturers, thereby making any transition to new blood collection methods more challenging than simply switching to a new source. This document provides provisional guidance for validating alternative sources of sodium citrate blood collection tubes (commercial or in‐house preparations) prior to clinical implementation.